2006
DOI: 10.1177/0013164405282483
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Dimensionality and Factor Structure of Multiple-Choice Exams

Abstract: Examination of a test's internal structure can be used to identify what domains or dimensions are being measured, identify relationships between the dimensions, provide evidence for hypothesized multidimensionality and test score interpretations, and identify construct-irrelevant variance. The purpose of this research is to provide a methodological comparison of three methods for assessing the dimensionality and factor structure for binary scored exams in which guessing may be operating. The factor analytic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Factor analyses applied to these data suggested that there was a single prominent dimension measured by the MBE. The finding of a single prominent dimension for the MBE is consistent with Stone and Yeh (2006).…”
Section: Unidimensionality Assumptionsupporting
confidence: 70%
“…Factor analyses applied to these data suggested that there was a single prominent dimension measured by the MBE. The finding of a single prominent dimension for the MBE is consistent with Stone and Yeh (2006).…”
Section: Unidimensionality Assumptionsupporting
confidence: 70%
“…For example, if there were no missing question responses identified, this would suggest that students either had good knowledge or were guessing for some questions. Conversely, if there were missing question responses, this might be either an indication of an inadequate time for completing the examination, a particularly hard exam or negative marking is being used (Stone & Yeh 2006;Reeve et al 2007).…”
Section: Individual Questionsmentioning
confidence: 99%